THE CHARACTERIZATION OF KAISO TRANSGENIC MICE - Bayer, Luke (My University, 2019)
Colitis-associated cancer (CAC) is a poorly characterized subgroup of colorectal cancers (CRC) that afflicts ~20% patients suffering from inflammatory bowel disease (IBD). The limited understanding of CAC stems from the lack of suitable mammalian model systems, as well as a general gap in knowledge regarding the molecular mechanisms of this disease. Currently, colitis is modelled by the use of the detergent dextran sodium sulfate (DSS) to induce inflammation in the intestines of mice. Studies have shown that increased expression of the transcription factor Kaiso causes intestinal inflammation and early-stage tumorigenesis in mice, even without additional intestinal insult. This inflammatory progression mimics the beginnings of CAC in humans, and we postulate that with a “second-hit” caused by a carcinogen such as azoxymethane (AOM), the mice will cross the threshold from inflammation to carcinogenesis. Wildtype (WT), KaisoTg mice, and APCmin/+/KaisoTg crossed mice were exposed to various combinations of the pro-inflammatory detergent DSS, the carcinogen AOM and the general anti-inflammatory, aspirin. Intestinal tissues were collected for gross morphological assessment, polyp quantification and Immunohistochemistry (IHC) analysis, in order to determine the relative expression level and localization of pro-inflammatory and tumorigenic proteins. We hypothesized that exposure to DSS or AOM will exacerbate Kaiso-mediated intestinal inflammation and lead to colitis-associated cancer (i.e. polyp formation), while aspirin will rescue the APCmin/+/KaisoTg accelerated tumour forming phenotype. KaisoTg treated with AOM or DSS exhibited an impeded weight gain phenotype, extensive intestinal hyperplasia and altered gene expression. IHC analysis revealed that two key adhesion proteins, p120ctn and E-Cadherin exhibit aberrant expression and localization in KaisoTg, independent of treatment. Additionally, it was observed that AOM treatment and Kaiso overexpression work synergistically to produce an ectopic expression profile for the proliferation marker, Ki67. Together these finding suggest a role for Kaiso in intestinal inflammation, cancer initiation via altered proliferation, and the destabilization of adherens junctions, leading to a compromised intestinal epithelial barrier.
The characterization of Kaiso transgenic mice, a potential model for the IBD-to-CAC transition.
Keywords: Kaiso; mice; zbtb33; inflammation; IBD; CRC; CAC; colitis; associated; cancer